The social production of suicide and the “social issue” in the reality of Iguatu (CE) - Albuquerque, Cynthia Studart; Matos, Rachel Araujo de (Argumentum, 2020)
The manuscript deals with the interface between the “social issue” and suicide and is based on the analysis of the living conditions of service users monitored by the Psychosocial Care Center in the city of Iguatu (CE). The qualitative research consists of a bibliographic review and documentary research, supported by content analysis, its sources being the health indicators of epidemiological surveillance data and the information contained in the medical records of the Personality, Self-Injury and Suicide Outpatient Clinic (PSSOC) of the Psychosocial Care Center (PCC III) in the municipality. As a result, we identified that in Iguatu (CE) there is a social production of suicide intersected by multiple expressions of the “social issue”. To confront this process, it is essential to defend democracy and rights as determinant issues for well-being and decent living and working conditions for the working class.